EFFECT OF PROTECTANT OF SOWING SEED TREATMENT ON SEED QUALITY AND YIELD OF SOFT WINTER WHEAT GRAIN - Герман, М. М.; Міщенко, О. В. (Scientific Progress & Innovations, 2013)
According to scientific research, it was found that the use of pre-treatment of wheat seeds of soft winter by bacterial substances polimiksobakteryn (150 ml/t) and diazofit (150 ml/t) and joint processing of growth regulators pennant (120 ml / t) and agate – 25K (60 g/t), against fertilizing N25P25K25, N50P50K50, N75P75K75 provides higher vigor, laboratory and field germination. According to scientific studies it was found that the use of presowing seed by treatment growth regulators Vympel (120 ml/t) and Аgate-25K (60 g/t) by fertilizing N75P75K75 vigor seeds 2.7%, 1.7% seed germination, survival soft winter wheat plants increased by 10.2%; by bacterial drugs: polimiksobakteryn (150 ml/t) –9.4%, diazofit (150 ml/t) by 9.3% , that exceeds control.